A Pre Study for Developing and Exploring An “Impulsive Buying Scale” for Turkish Population - Ertugrul Godelek; Fatih Akalın (European Scientific Journal, ESJ, 2018)
Impulsive buying has 4.2 billion US $ trading volume a year in the USA. First researches about impulsive buying had been conducted between 1945 and 1965 as Unplanned Buying by DuPont Customer Buying Researches in the USA. In the researches conducted for over sixty years, many definitions of compulsive buying have been given. Verplanken and at all. (2011), Rook at all., (1995) defined impulsive buying as unneeded and unreflective buying which occurs under the impulse of the moment. The purpose of this research is twofold; one of which is to develop a valid and reliable “Impulsive Buying Scale”, and the second is to investigate the effect of demographic and socioeconomic variables on impulsive buying by using the aforementioned scale. For this reason, “Impulsive Buying Scale” was applied to 800 participants who live in Mersin. Construct Validity was used to evaluate the validity of scale; the Cronbach’s Alpha was used to evaluate the reliability of scale. According to the findings, a valid and reliable scale, which can be used to measure impulsive buying, was obtained. In addition to this finding, it was also found that some socio-economical and demographical variables affected impulsive buying.